Pengaruh Profitabilitas, Struktur aset, Risiko bisnis dan kapasitas pelayanan hutang terhadap struktur modal pada perusahaan Manufaktur di Bursa Efek Indonesia (BEI) Periode 2017-2019. - Silvia Sahara; Ronny Malavia Mardani; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the relationship between profitability, asset structure, business risk and debt service capacity to the company's capital structure. This type of research is explanatory research. The data used is secondary data obtained by documentation techniques, namely by searching and collecting financial report data obtained from the website. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period with a total of 39 companies. While the sample in this study was determined by purposive sampling technique in order to obtain 21 sample companies. The data analysis technique in this research uses multiple linear regression method.The results of this analysis indicate that profitability has no significant negative effect on the company's capital structure. Asset structure has no significant negative effect on the company's capital structure. Business risk has no significant negative effect on the company's capital structure. Debt service capacity has no significant positive effect on the company's capital structure. Meanwhile, profitability, asset structure, business risk and debt service capacity simultaneously have a significant effect on the company's capital structure. Keywords: Profitability, Asset Structure, Business Risk, Debt Service Capacity and Capital Structure.